PENGUKURAN TEKANAN DAN WAKTU PADA PERANCANGAN BIODIGESTER LIMBAH CAIR PABRIK TAHU - Hadrah Hadrah (Universitas Batanghari Jambi, 2017)
The liquid waste produced by the tofu industry is organic waste which is degradable or can be naturally decomposed by microorganisms. This study aims to measure the volume of tofu industrial wastewater required to produce biogas with a certain pressure so that the liquid waste used as raw material can be utilized optimally. In addition, testing the content of TSS, ammonia, BOD5, COD, and pH in tofu waste in the process of processing it into biogas was also carried out. Experiments were carried out using a biodigester to create anaerobic conditions for tofu waste. The presence of the decomposition gas is detected using a simple manometer. In addition, the possibility of methane gas is estimated by conducting a flame test. The variation of the composition of tofu waste and cow dung (starter) with volume ratio in the biodigester is without starter on Gallon I and Drum I, using a 2% starter on Drum II, and using a 10% starter on Gallon II. The experimental results showed that each biodigester drum I, drum II, gallon I and gallon II produced maximum pressures of 2,158.2 Pa, 42,844.9 Pa, 1863.9 Pa, and 3,629.7 Pa. The maximum retention time for each biodigester drum I, drum II, gallon I, and gallon II was 53 days, 43 days, 58 days and 49 days. The flame test conducted showed that there was only a flame in the biodigester with the addition of a starter material of 10%. Processing of tofu waste into biogas without a starter can reduce the pollutant content, namely TSS and ammonia by 96.5% and 96%, whereas with a starter of 2% by 95% and 94%, and with a starter of 10% by 91% and 95%. Likewise with BOD and COD parameters, the reduction in waste without starter was 96% and 97%, with a starter of 2% by 96% and 96%, and with a starter of 10% by 97% and 98%. The increase in pH occurred in waste without starter to 0.99, waste with a starter of 2% was 1.65 and waste with a starter of 10% was 1.27.